Preliminary phytochemical screening, antihyperglycemic, analgesic and toxicity studies on methanolic extract of aerial parts of Corchorus olitorius L. - Sanjida Parvin, Moytry Marzan, Sanjana Rahman, Anuj Kumer Das, Sanjida Haque, Mohammed Rahmatullah (Journal of Applied Pharmaceutical Science, 2015)
Corchorus olitorius, also known as Nalta jute or Tossa jute is grown throughout Bangladesh for its fibre and because the aerial parts are edible. It was of interest to phytochemically screen and conduct antihyperglycemic, analgesic and toxicity studies of the aerial parts. Antihyperglycemic and analgesic activities, phytochemical screening and toxicity studies were done through standard methods. Administration of methanol extract of aerial parts (MECO) led to dose-dependent reductions in blood glucose levels in glucose-loaded mice. At doses of 50, 100, 200 and 400 mg per kg, the extract reduced blood glucose levels by 18.6, 29.3, 32.9, and 50.7%, respectively compared to control animals. By comparison, a standard antihyperglycemic drug, glibenclamide, when administered at a dose of 10 mg per kg, reduced blood glucose level by 48.9%. In analgesic activity tests, MECO at doses of 50, 100, 200 and 400 mg per kg reduced the number of writhings by 19.2, 42.3, 53.8, and 57.7%, respectively. A standard analgesic drug, aspirin, reduced the number of writhings by 38.5 and 65.4%, respectively, when administered at doses of 200 and 400 mg per kg. Phytochemical screening of MECO showed presence of alkaloids, flavonoids, saponins and tannins, which may be responsible for the observed effects.
Keywords: Antihyperglycemic, Corchorus olitorius, analgesic, Tiliaceae.